A new synonymy in the fidius group of Copris Müller 1764 (Coleoptera: Scarabaeidae: Scarabaeinae) and a new species from the highland grasslands of South Africa - Deschodt, Christian M.; Davis, Adrian L.v.; Scholtz, Clarke H. (Zootaxa, 2015)
The fidius group constitutes the basal clade in a phylogeny of the Afrotropical members of the genus, Copris Müller, 1764. In this paper we describe Copris crassus Deschodt and Davis as a new species in this group. We also demonstrate that the distributional function between two body dimensions (lateral horn length and mid-line elytron length) differs between Copris fidius (Olivier 1789) and C. crassus. Copris bihamatus Balthasar, 1965 is also a member of the fidius group. Nguyen-Phung (1988) suspected that it was a synonym of C. fidius (Olivier) so we compare specimens of similar body size and use the distributional function between body dimensions to demonstrate that C. bihamatus is indeed a synonym of C. fidius. We provide a key for all known valid species in the fidius group, except C. serius Nguyen-Phung, 1987.